The effect of adapting listening tasks in Tieng Anh 11 textbook - A case study of an upper secondary school in the Mekong Delta : - Kiều, Thị Thu Trinh (Can Tho University, 2015)
Investigate students' attitudes toward listening tasks in Tieng Anh 11 textbook and the difficulties they met, and whether the targeted adaption could help improve students' listening comprehension and motivation